2021
DOI: 10.1155/2021/3548706
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Protection of Radiotherapy Induced Sensorineural Hearing Loss for Head and Neck Cancer

Abstract: Purpose. Radiotherapy-induced sensorineural hearing loss (RISNHL) is a common adverse effect in patients with head and neck cancer. Given that there are few studies on the pathogenesis of RISNHL at present, we summarized the possible pathogenesis of RISNHL and possible protective measures found at present by referring to relevant literatures. Methods. We performed a comprehensive literature search in the PubMed database, using keywords “sensorineural hearing loss,” “radiotherapy,” and “cancer,” among others. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 98 publications
0
12
0
Order By: Relevance
“…Inevitably these side-effects reduce the quality of life of the cancer survivors. For a long time, the radiation dose received by the cochleae was considered to be responsible for the damage [ 4 ]. In our previous study [ 7 ], we found that the radiation-induced inflammatory response was involved in the damage to the cochleae and subsequent SNHL, but the mechanisms were not completely elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inevitably these side-effects reduce the quality of life of the cancer survivors. For a long time, the radiation dose received by the cochleae was considered to be responsible for the damage [ 4 ]. In our previous study [ 7 ], we found that the radiation-induced inflammatory response was involved in the damage to the cochleae and subsequent SNHL, but the mechanisms were not completely elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…For a long time, the radiation dose to the inner ear was considered to be responsible for the damage to the cochlea and SNHL [ 4 ]. However some studies have reported that the inflammatory response induced by radiation can cause apoptosis of hair cells of the inner ear [ 5 ], and a large number of inflammatory cells appear in the inner ear of irradiated experimental animals [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, radiotherapy to head and neck tumors, such as nasopharyngeal carcinoma (NPC), often inevitably damages the adjacent organs of auditory, which may further increase the risk of hearing loss (HL). Previous studies reported that both platinum and radiation could contribute to DNA damage to auditory cells (Mujica-Mota et al 2014 ), leading to apoptosis and death of hair cells, stria vascularis endothelial cells, and spiral ganglion neurons (Landier 2016 ; Shi et al 2021 ). Platinum-based concurrent chemoradiotherapy has been recommended as the standard treatment modality for advanced NPC (Pfister et al 2020 ), a malignancy particularly prevalent in the east and southeast Asia, especially in Southern China (Chen et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a previous study showed that 72.3% of patients with HN cancers treated with radiotherapy developed hearing loss (9). The incidence of radiation-induced SNHL varies and depends on various factors, including radiation dose, patient age, and hearing sensitivity (10). A cumulative body of literature has demonstrated that the high incidence of SNHL positively correlates with the administration of radiotherapy.…”
Section: Introductionmentioning
confidence: 99%